Chromium-nickel coating based on CeO2 and Y2O3 modification and preparation method thereof

By adding CEO2 and Y2O3 to chromium nickel coatings, and using laser melting technology, the existing chromium nickel coatings have insufficient corrosion resistance in the high -temperature flue gas environment, and achieve higher corrosion resistance and coating. Layer -binding strength.

CN119352009APending Publication Date: 2025-01-24HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411286862.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing chromium-nickel coating is not suitable for high-temperature, long-term, low-stress flue gas service environments, and the stability of Cr2O3 in high-temperature steam is poor, resulting in reduced oxide film peeling and corrosion resistance.

Method used

Adopt chromium -nickel coating preparation methods based on CEO2 and Y2O3 modifications, by adding CEO2 and Y2O3 to the solid -phase melting powder, and using laser melting processes to prepare the coating force.

Benefits of technology

Improved the corrosion resistance of chromium nickel coating. The weight loss of 200 hours in the engineer of the workpiece in the flue gas environment is only 2 % to 10 % of the mother material, and the intensity of the coating and the mother material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352009A_ABST
    Figure CN119352009A_ABST
Patent Text Reader

Abstract

The invention discloses a chromium-nickel coating based on CeO2 and Y2O3 modification and a preparation method of the chromium-nickel coating. Cladding slurry is uniformly sprayed to the surface of a workpiece, and a chromium cladding coating is obtained through laser cladding; wherein the cladding powder comprises the following components in percentage by mass: 40 to 70 percent of Cr, 20 to 50 percent of Ni, 0 to 5 percent of CeO2, 0 to 5 percent of Y2O3 and 1 to 5 percent of NH4Cl. The prepared chromium-nickel coating is uniform in organization structure, moderate in thickness, sufficient in Cr atom diffusion, good in metallurgical bonding with a base body, not prone to falling off, good in corrosion resistance and suitable for austenitic steel and high-temperature alloy parts used for workpieces with the large length-diameter ratio and various complex shapes such as large boilers and oil and gas field conveying pipelines. And the method has excellent industrial batch production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface alloying and coating preparation, and specifically relates to a chromium-nickel coating based on CeO2 and Y2O3 modification and a preparation method thereof. Background Art

[0002] The cost of my country's thermal power generation industry has increased by more than 20% due to the oxidation of the inner wall of the flow components and the flue gas corrosion of the outer wall. The corrosion of the flow components with a large aspect ratio has become a common industry problem and technical pain point that restricts the safe production and operation of the entire energy equipment. Studies have shown that high-temperature coatings have obvious effects in solving the oxidation corrosion, wear, and high-temperature ablation of components; therefore, the industry currently adopts the method of preparing chromium-nickel corrosion-resistant coatings on the surface of austenitic steel pipes to address the problem of flue gas corrosion on the outer wall of pipes used in boiler units.

[0003] However, the existing chromium-nickel coating preparation technology is not suitable for large aspect ratio structural flow components in high temperature, long time, low stress flue gas service environment. On the other hand, as far as the chromium-nickel coating itself is concerned, the stability of Cr2O3 in steam above 600℃ is poor, and the loose oxide film caused by volatile products will cause the oxide film to peel off, and further lead to pipe blockage and pipe explosion accidents; in addition, the Cr content in the alloy matrix is ​​relatively low. With the increase of service time, when the Cr content required for the growth of the oxide film cannot be replenished, the corrosion resistance of the alloy will also drop sharply. Therefore, it is of great practical significance to study and develop the preparation technology of chromium-nickel coating suitable for the surface of large aspect ratio flow components, and to develop modification technology to improve the corrosion resistance of chromium-nickel coating in complex service environment. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a chromium-nickel coating based on CeO2 and Y2O3 modification.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] The solid phase cladding powder is mixed with the liquid phase binder and ball milled to obtain the cladding slurry;

[0009] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to be plated, and naturally dried and cured to obtain the coated workpiece;

[0010] After the workpiece is cooled, a chromium cladding coating is obtained.

[0011] The raw materials of the solid phase cladding powder include, by mass percentage, 40-70% Cr, 20-50% Ni, 0-5% CeO2, 0-5% Y2O3, and 1-5% NH4Cl. The raw materials are ball-milled at 350-400rpm for 12-24h to obtain the solid phase cladding powder.

[0012] As a preferred solution of the method for preparing the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the liquid phase binder is ethyl acetate, and the mass of the ethyl acetate is 10-30% of the solid phase cladding powder.

[0013] As a preferred solution of the method for preparing the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the stirring time is 2 to 4 hours.

[0014] As a preferred solution of the method for preparing the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the rotation speed of the ball mill is 350-400 rpm and the time is 8-12 hours.

[0015] As a preferred solution of the method for preparing the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes.

[0016] As a preferred solution of the method for preparing the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the spraying thickness of the cladding slurry is 1 to 5 mm, and the coating coverage is not less than 98%.

[0017] As a preferred embodiment of the method for preparing the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the curing temperature is 300-450°C and the curing time is 24-48 hours.

[0018] As a preferred scheme of the preparation method of the chromium-nickel coating modified by CeO2 and Y2O3 described in the present invention, the laser power of the laser cladding is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 3-6r / min, and the Ar gas flow rate is 15-20L / min.

[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a chromium-nickel coating prepared by a preparation method of a chromium-nickel coating modified by CeO2 and Y2O3, wherein: the thickness of the chromium-nickel coating is 0.32 to 1.71 mm, the Cr atomic content is 39.6 to 71.0%, and the Ni atomic content is 20.4 to 51.5%.

[0020] As a preferred solution of the chromium-nickel coating described in the present invention, the chromium-nickel coating improves the corrosion resistance of the workpiece, and the weight loss of the workpiece in a flue gas environment for 200 hours is only 2% to 10% of the base material.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention adds halide NH4Cl to the slurry components to achieve the effects of catalysis and activation, thereby improving the penetration rate and coating quality.

[0023] (2) The present invention promotes the diffusion of the coating and improves the bonding strength of the membrane substrate by adding rare earth oxides CeO2 and Y2O3 to the cladding powder components.

[0024] (3) The present invention prepares the coating through a laser cladding process, which has concentrated heat, short action time, small thermal impact in the cladding zone, and high bonding strength between the coating and the base material.

[0025] (4) The present invention prepares the coating through an integrated laser cladding process production line, and the coating production efficiency is high, the thickness is controllable, the process repeatability is high, and it has strong practicality and universality.

[0026] (5) The addition of rare earth oxides can pin the grain boundaries, strengthen the matrix structure, improve the surface hardness, and enhance the bonding strength between the coating and the base material in the form of second phase precipitation on the basis of halide-promoted diffusion. In addition, rare earth oxides can reduce the critical concentration of Cr to form Cr2O3 oxide film.

[0027] (6) The segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of micro cracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0029] Figure 1This is a cross-sectional morphology diagram of the laser cladding chromium-nickel coating prepared by the rare earth oxide modification method in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0033] The model of the instrument used for laser cladding in the present invention is: Laser Cladding Equipment Jinweike Laser Technology Co., Ltd., model: GKS-LC3008R.

[0034] The workpiece to be plated in the present invention is a Super304H seamless steel pipe purchased from the market, and its main alloy components and contents are: Cr18.18%, Ni9.02%, Cu2.99%, Nb0.47%, Si0.16%, Mn0.80%, B0.0039%, and N0.094%.

[0035] The method for measuring the thickness of the chromium coating in the present invention is: using a scanning electron microscope SEM (model Zeiss-Sigma HD) and a backscattering HDBSD (model Zeiss-Sigma HD) to measure the thickness of the chromium coating according to the magnification and the scale.

[0036] The method for determining the atomic content of Cr and Ni in the chromium coating of the present invention is: using a scanning electron microscope SEM (model Zeiss-Sigma HD) with energy spectrum EDS (model Oxford) and backscattering HDBSD (model Zeiss-Sigma HD) to determine the Cr and Ni content of the coating.

[0037] The method for determining the corrosion resistance of the material of the present invention under high temperature conditions is as follows: in a 650°C synthetic coal ash and synthetic flue gas environment, the coal ash composition SiO247.36%, A l2O323.96%, Fe2O316.50%, CaO 4.06%, MgO 1.38%, Na2SO41.81%, K2SO41.18%, TiO22.94%, flue gas components CO212.600%, CO 2.100%, SO20.296%, N274.640%, H2O 6.510%, O23.780%; fly ash is fully ground in a mortar and diluted with alcohol to form a suspension, and the amount of fly ash applied is controlled to be about 20mg / cm 2 The synthetic flue gas introduction rate was 1 L / min. After 200 hours, a sample was taken out, washed in boiling water for 48 hours, dried and weighed.

[0038] The quantitative index of the corrosion resistance of the material of the present invention is the weight loss per unit area under a corrosive environment. The calculation method is as follows: the weight loss per unit area (in mg / cm2) is calculated after 200 hours in a synthetic coal ash and synthetic flue gas environment at 650°C. 3 ) to evaluate the corrosion resistance of materials.

[0039] Example 1

[0040] This embodiment provides a method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3.

[0041] The solid phase components, including 40% Cr, 50% Ni, 4% CeO2, 4% Y2O3 and 1% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for 12 hours at 400 rpm to obtain solid phase cladding powder; then, 10% ethyl acetate was added and fully stirred for 4 hours, and then placed in a planetary ball mill for 12 hours at 400 rpm to obtain a uniformly mixed slurry, which is the cladding slurry.

[0042] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 3mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours and cure it at 450°C for 48 hours.

[0043] The workpiece was placed under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 20L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0044] Figure 1 This is a cross-sectional morphology of the laser cladding chromium-nickel coating in this embodiment. It is found that the coating has a uniform structure, moderate thickness, sufficient diffusion of Cr atoms, good metallurgical bonding between the coating and the substrate, and is not easy to fall off.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that the laser cladding parameters are adjusted, and the other steps and processes refer to embodiment 1 to obtain chromium-nickel coatings under different laser cladding parameters. The laser cladding parameters, i.e., the corresponding coating-related indicators, are shown in Table 1.

[0047] Table 1 Performance comparison of chromium-nickel coatings under different laser cladding parameters

[0048]

[0049] As shown in Table 1, the thickness of the chromium-nickel coating is 0.85-1.68 mm, the coating has a uniform structure, moderate thickness, sufficient diffusion of Cr atoms, good metallurgical bonding between the coating and the substrate, and is not easy to fall off. -1 , the diameter of the optical beam is 4 mm, and the Ar flow rate is 20 L min -1 , the workpiece rotation speed is 5r·min -1 Under these conditions, the prepared chromium-nickel coating has the best corrosion resistance, and the weight loss in the flue gas environment for 200 hours is only 0.10 mg / cm 3 .

[0050] Example 3

[0051] This embodiment provides a method for preparing a chromium-nickel coating based on CeO2 modification.

[0052] The solid phase components, including 70% Cr, 20% Ni, 5% CeO2 and 5% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 350 rpm for 24 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 12 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0053] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 300°C for 48 hours.

[0054] The workpiece was placed under Ar for laser cladding, with a laser power of 2.5KW, a scanning rate of 20mm / s, a spot diameter of 2mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0055] Example 4

[0056] This embodiment provides a method for preparing a chromium-nickel coating based on Y2O3 modification.

[0057] The solid phase components, including 40% Cr, 50% Ni, 5% Y2O3 and 5% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder; then, 20% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill at 350 rpm for 8 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0058] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 30 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 2mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0059] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0060] Example 5

[0061] This embodiment provides a method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3.

[0062] The solid phase components, including 60% Cr, 25% Ni, 5% CeO2, 5% Y2O3 and 5% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for 12 hours at 400 rpm to obtain solid phase cladding powder; then, 20% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for 12 hours at 350 rpm to obtain a uniformly mixed slurry, which is the cladding slurry.

[0063] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 400°C for 48 hours.

[0064] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0065] Example 6

[0066] This embodiment provides a method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3.

[0067] The solid phase components, including 55% Cr, 32% Ni, 3% CeO2, 4% Y2O3 and 6% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 400 rpm for 24 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 2 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 12 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0068] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes at medium frequency, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%; then, air-dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0069] The workpiece was placed under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 30mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 18L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0070] Example 7

[0071] This embodiment provides a method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3.

[0072] Solid phase components, including 40% Cr, 50% Ni, 4% CeO2, 4% Y2O3 and 2% NH4Cl, were weighed according to mass proportion and placed in a planetary ball mill for ball milling at 350 rpm for 12 h to obtain solid phase cladding powder; subsequently, 30% ethyl acetate was added and fully stirred for 4 h and then placed in a planetary ball mill for ball milling at 400 rpm for 8 h. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0073] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes at medium frequency, and use spraying to pre-set the slurry layer thickness to 4mm, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 36 hours and cure it at 450°C for 48 hours.

[0074] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 20L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0075] Example 8

[0076] This embodiment provides a method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3.

[0077] The solid phase components, including 65% Cr, 25% Ni, 2% CeO2, 4% Y2O3 and 4% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 350 rpm for 24 hours to obtain solid phase cladding powder; then, 20% ethyl acetate was added and fully stirred for 4 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 8 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0078] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours and cure it at 450°C for 48 hours.

[0079] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 4mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the workpiece surface was flushed with high-pressure airflow.

[0080] Example 9

[0081] This embodiment provides a method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3.

[0082] The solid phase components, including 55% Cr, 35% Ni, 4% CeO2, 2% Y2O3 and 4% NH4Cl, were weighed according to the mass ratio, and placed in a planetary ball mill for ball milling at 400 rpm for 24 hours to obtain solid phase cladding powder; then, 30% ethyl acetate was added and fully stirred for 4 hours, and then placed in a planetary ball mill for ball milling at 400 rpm for 8 hours. After completion, a uniformly mixed slurry was obtained, which is the cladding slurry.

[0083] Use a high-pressure water gun to clean the surface of the workpiece for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 60 minutes at medium frequency, use spraying to pre-set the slurry layer thickness to 5mm, and keep the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0084] The workpiece was placed under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 35mm / s, a spot diameter of 4mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 18L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was flushed with high-pressure airflow.

[0085] The smoke corrosion resistance of the workpieces containing chromium and nickel coatings was measured. The performance comparison of the coatings prepared in Examples 3-9 is shown in Table 2.

[0086] Table 2 Comparison of chromium-nickel coating properties in Examples 3-9

[0087]

[0088]

[0089] As shown in Table 2, taking Super304H as an example, the weight loss in the smoke environment for 200h is 3.5mg / cm 3 The oxidation corrosion resistance of the workpieces coated with chromium-nickel coatings in Examples 3-9 is improved by more than 10 times.

[0090] Combining Tables 1 and 2, the thickness of the prepared chromium-nickel coating is 0.32-1.71 mm, the Cr atomic content is 39.6-71.0%, and the Ni atomic content is 20.4-51.5%; the chromium-nickel coating improves the corrosion resistance of the workpiece, and the weight loss of the workpiece in a flue gas environment for 200 hours is only 2%-10% of the base material.

[0091] Comparative Example 1

[0092] The difference between this comparative example and Example 1 is that the solid phase component does not contain Y2O3 and CeO2, and the other steps are the same as those in Example 1 to prepare the chromium-nickel coating.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that the solid phase component does not contain CeO2, and the other steps are the same as those in Example 1 to prepare the chromium-nickel coating.

[0095] The performance comparison of chromium and nickel coatings is shown in Table 3.

[0096] Table 3 Comparison of chromium-nickel coating performance

[0097]

[0098] As shown in Table 3, the chromium-nickel coating prepared in Example 1 has a much lower weight loss than the control example in a 200h flue gas environment, and has good corrosion resistance.

[0099] In summary, the present invention achieves the effects of catalyzing and activating the infiltration and improving the infiltration rate and coating quality by adding halide NH4Cl to the slurry component; the rare earth oxides CeO2 and Y2O3 are added to the cladding powder component to promote the diffusion of the coating and improve the bonding strength of the membrane substrate; the coating is prepared by a laser cladding process, which has concentrated heat, short action time, small thermal impact in the cladding zone, and high bonding strength between the coating and the parent material; the coating is prepared by an integrated laser cladding process production line, which has high coating production efficiency, controllable thickness, high process repeatability, and strong practicality and universality; the addition of rare earth oxides can pin grain boundaries, strengthen matrix structure, improve surface hardness, and improve the bonding strength between the coating and the parent material in the form of second phase precipitation on the basis of halide-promoted diffusion; in addition, rare earth oxides can reduce the critical concentration of Cr to form Cr2O3 oxide film.

[0100] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3, characterized in that: include, The solid phase cladding powder is mixed with the liquid phase binder and ball milled to obtain the cladding slurry; The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to be plated, and naturally dried and cured to obtain the coated workpiece; After the workpiece is cooled, a chromium cladding coating is obtained. The raw materials of the solid phase cladding powder include, by mass percentage, 40-70% Cr, 20-50% Ni, 0-5% CeO2, 0-5% Y2O3, and 1-5% NH4Cl. The raw materials are ball-milled at 350-400rpm for 12-24h to obtain the solid phase cladding powder.

2. The method for preparing a chromium-nickel coating based on CeO2 and Y2O3 modification according to claim 1, characterized in that: The liquid phase binder is ethyl acetate, and the mass of the ethyl acetate is 10-30% of the solid phase cladding powder.

3. The method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3 according to claim 1, characterized in that: The stirring time is 2 to 4 hours.

4. The method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3 according to claim 1, characterized in that: The ball mill has a rotation speed of 350-400 rpm and a milling time of 8-12 hours.

5. The method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3 according to claim 1, characterized in that: The preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.

6. The method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3 according to claim 1, characterized in that: The spraying thickness of the cladding slurry is 1-5 mm, and the coating coverage is not less than 98%.

7. The method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3 as claimed in claim 1, characterized in that: The curing temperature is 300-450° C. and the curing time is 24-48 hours.

8. The method for preparing a chromium-nickel coating based on modification of CeO2 and Y2O3 according to claim 1, characterized in that: The laser power of the laser cladding is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 3-6r / min, and the Ar gas flow rate is 15-20L / min.

9. The chromium-nickel coating prepared by the method for preparing a chromium-nickel coating modified by CeO2 and Y2O3 according to any one of claims 1 to 8, characterized in that: The thickness of the chromium-nickel coating is 0.32-1.71 mm, the Cr atomic content is 39.6-71.0%, and the Ni atomic content is 20.4-51.5%.

10. The chromium-nickel coating according to claim 9, characterized in that: The chromium-nickel coating improves the corrosion resistance of the workpiece, and the weight loss of the workpiece in a flue gas environment for 200 hours is only 2% to 10% of the base material.

Citation Information

Cited By

  • Modification method for improving corrosion resistance of chromium-nickel cladding coating

    CN120006280A